Strategi Pengasuh Dalam Mengembangkan Pendidikan Karakter Pondok Pesantren As – Salma Bahrul Ulum Tambakberas Jombang - Waslah, Waslah; Aprilyanti, Vina (Universitas KH. A. Wahab Hasbullah, 2023)
The purpose of this study was to find out the caregiver's strategy in developing character education period as well as the supporting and inhibiting factors at the Pondok Pesantren Putri As - Salma Bahrul Ulum Tambakberas Jombang. The approach used in this research is a qualitative approach with the type of case study research. The method used is observation, interviews, and documentation. The data analysis technique uses a qualitative descriptive analysis technique. The caregiver's strategies in developing character education for students at the Putri As - Salma Bahrul Ulum Islamic Boarding School Tambakberas, include: looking for quality teachers, good communication, showing exemplary, educating students with habits, fixing management. The supporting factor is the prohibition on leaving the Islamic boarding school, so that students are protected from outside influences. The inhibiting factor is the activities of students who are limited to Islamic boarding schools, so that the development of character education for students is not optimal. The results of this study indicate that the caregiver's strategy in developing character education for students is good and activities in Islamic boarding schools are able to support the development of character education for students.